A multidimensional approach to measuring household food security in Taraba State, Nigeria: comparing key indicators. Issue 2 (17th February 2017) - Ike, Chinweoke Uzoamaka; Jacobs, Peter T.; Kelly, Candice
ABSTRACT: This study used household data from Taraba State, Nigeria, to explore the advantages of using a multidimensional approach to measure food and nutrition insecurity. Adaptations of three popular food security indicators were combined in a single household questionnaire to test how well the Household Food Insecurity Access Scale (HFIAS), the Dietary Diversity Score (DDS), and the Coping Strategies Index (CSI) complement each other. Sixty-nine per cent of households in the sample were classified as extremely food insecure, which means they are likely to resort to intensive but erosive coping strategies and lower dietary diversity. The three indicators powerfully complemented each other. This multidimensional food security measurement framework provided a more nuanced picture of the depth and breadth of food insecurity for local government areas in Taraba State. This approach can help Nigerian policy authorities overcome the information deficits that impede effective food and nutrition assistance interventions.